Fiscal sustainability duringthe COVID-19 pandemic - Patrick Hürtgen (Deutsche Bundesbank, 2020)
The "Great Lockdown" implemented in response to the COVID-19 pandemic has led to a severe world-wide economic crisis. In euro area countries, sovereign debt-to-GDP ratios are on the rise and reductions in expected fiscal surpluses raise sustainability concerns amongst investors. This paper provides novel estimates of non-linear state-dependent fiscal limits based on Bi (2012) for the five largest euro area countries. Within the DSGE model I build a COVID-19 scenario calibrated to match the decline in real GDP growth forecasts between April and February2020 and the fiscal stimulus packages announced up to the end of March 2020. On average, fiscal space contracts by 58.4 percent of national GDP. In a worst-case scenario fiscal space is 28.6 percent for Italy and 65.9 percent of national GDP for Germany.
Keywords: E32; H30; H60; 330; state-dependent fiscal limits; fiscal space; sovereign debt; Laffer curve; COVID-19